BIMBINGAN PRIBADI UNTUK MENINGKATKAN PENERIMAAN DIRI SISWA : StudiDeskriptifTerhadapSiswaKelasVIII SMPNegeri 19 Bandung TahunAjaran 2012/2013 - Angraini, Fahmi Dewi (2013)
The study was originated by the important of individual's self acceptance especially the Junior High School students. The study purposed to get the general description of students' self acceptance and to produce personal guidance program to improve students' self acceptance. The study used quantitative with descriptive method. The results of the study are: (1) descriptions of students' self acceptance of 8th generally was on medium category, (2) program descriptions of personal guidance and counseling of 8th SMP Negeri 19 Bandung for the period 2012/2013; and (3) the implication of self acceptance profile for guidance and counseling was arranged on personal guidance program to improve students' self acceptance 8th of SMP Negeri 19 Bandung. Key words: personal guidance program, self acceptance